The total polyphenolic glycoside extract of Lamiophlomis rotata ameliorates hepatic fibrosis through apoptosis by TGF-β/Smad signaling pathway - Guoguo Wan; Zhiwei Chen; Lei Lei; Xiaoyu Geng; Yi Zhang; Congwen Yang; Wenfu Cao; Zheng Pan (BMC, 2023)
Highlights Chemical composition of TPRL was identified by UPLC-Q/TOF/MSn in the profile of total ion current. TPRL was initially demostrated the effects of anti-hepatic fibrosis in vitro and in vivo. TPRL ameliorates hepatic fibrosis through apoptosis by TGF-β/Smad signaling pathway.